Right Issue and Dilution Matters in Banking Equity Market: Study of PT Bank Mandiri (Persero) Tbk - Albar, Arasyan; Nugroho, Anggoro Budi (Journal of Business and Management, 2015)
Abstract. Banking industry has specific regulation on their capital requirements according to Basel Accord agreements that bank must keep their amount of capital balanced with the total risk assets in lots of requirement criteria especially Capital Adequacy Ratio (CAR). In order to fulfil this requirement, the only way banks could raise fund with capital is Initial Public Offering (IPO) for the unlisted company and Right Issue for listed company. Since PT. Bank Mandiri (Persero) Tbk, is the biggest assets bank in the country, the only way to rise this source funding is right issue if they want to maintain their amount of capital. Right issue is preemptive right for the investor to keep their ownership percentage to prevent it from share dilution as the company raised more shares to the market. However, not everyone is aware of the possibly wealth dilution as the rising amount of shares sold at the lower price where at this research commonly called â€œvalue dilutionâ€. The research objective is to determine how variables in right issue are interacting, Bank Mandiriâ€™s value of right issue and the value dilution as well (with comparison with similar industry at the same year), value dilution Â factors that determine value dilution of right issue decisions, also the forecast of future right issue on Bank Mandiriâ€™s plan in 2018. Theoretical right price and theoretical ex-right price have been used as the base of formula and calculation in the research developed with simulation of various number of independent variable such as subscription price and exchange ratio to find result in the correlation of these variables to the value dilution. Also, forecast of following Bank Mandiriâ€™s right issue in 2018 used the same formula but through different process where the current price in the future has to be estimated first and the number of issued share has to be determine to forecast the possibly value dilution and choose the best combination of subscription price and exchange ratio. Findings on this research reveal that Bank Mandiri has the highest right value and total wealth value dilution among the other similar industry company that done the similar corporate action at the same year (2011, compared with Bank Bukopin, Bank Danamon, and Bank QNB) while the share exchange ratio (N) is determining factor for the value dilution as the new share calculation in fraction result will affect the existence of value dilution. If the N resulting fraction number of new shares, subscription price will make the bigger value dilution as it going lower than the current market share. However, despite of value dilution increase it makes the right value increasing as well. Recommendation of following right issue in 2018 for Bank Mandiri is they can set the price of the subscription price between Rp8,562 to Rp17,425 per share if assumed they raise the amount of new share same as the right issue before in 2011 where they issued 2.336 billion of shares (so the N would be 9.889). However if company decided not to raise the amount of share same as previous right issue, company can issue 1,538,461,538 shares (with ratio 100 for 1501 shares) with the subscription price in Rp13,000.Â Keywords: Right issue, Bank Mandiri, BMRI, Theoretical Right Price, Theoretical Ex-Right Price.